A Comparative Study of Observer-Based State-of-Charge Estimation using Single-Particle Model with Electrolyte Dynamics and Equivalent Circuit Model of Lithium-ion Cells. Issue 1 (2022) - Nath, Anirudh; Mehta, Rohit; Gupta, Raghvendra; Bahga, Supreet Singh; Gupta, Amit; Bhasin, Shubhendu
Abstract: Various techniques have been implemented for battery state-of-charge estimation over the years, with the most common being the equivalent-circuit model (ECM). Among the physics-based models, the single-particle model (SPM) has found regular usage for state-of-charge estimation. The observers designed using the ECM and a recently developed physics-based models incorporating electrolyte dynamics for high C-rate applications are compared in this work. The results demonstrate improvement in the estimation performance of the observer by 7% for the proposed SPM as compared to ECM. The SoC estimation under the influence of measurement noise are also investigated for different ambient temperatures.